Abdominal Cystic Echinococcosis Treated with Albendazole. A Pediatric Cohort Study - Moroni, Samanta (2016)
INTRODUCTION:Cystic echinococcosis is endemic in Argentina. The standard pharmacological treatment for the disease is albendazole, but surgery is a common alternative. Even though primary infection occurs mainly in the pediatric population, the optimal therapeutic option in pediatrics is not clearly defined and few pediatric cohorts with cystic echinococcosis treated with albendazole have been described to date.OBJECTIVE:To describe therapeutic response to albendazole in a cohort of pediatric patients with abdominal cystic echinococcosis.POPULATION AND METHODS:Patients (0-18 years old) with abdominal cystic echinococcosis who were treated with albendazole between January 1998 and August 2013. Diagnosis of abdominal cystic echinococcosis was made by ultrasound. All patients received albendazole, 10-15 mg/kg/day. Epidemiological data, symptoms, number, location and outcome of the cysts, serology and treatment received were analyzed. The parameter used to assess treatment response was cyst changes evaluated by ultrasound follow up using the WHO-IWGE classification.RESULTS:A total of 28 patients (with 46 abdominal cysts) were included in the cohort. Mean age at enrolment was 9.4 years and mean duration of follow-up, 23.8 months. All patients resided in rural areas and had had contact with dogs. The asymptomatic form of the disease was the most common presentation. All patients received albendazole (mean duration: 142.5 days), with low incidence of adverse events. Albendazole had a positive effect on most of the cysts. Surgery was performed in 13 patients.CONCLUSION:Treatment with albendazole for uncomplicated cystic echinococcosis cysts is safe and effective, and can potentially reduce the need for surgical intervention